Language contact in the territory of the former Soviet Union - Forker, Diana; Grenoble, Lenore A. (Impact, studies in language and society ;, 2021)
"The former Soviet Union (USSR) provides the ideal territory for studying language contact between one and the same dominant language (Russian) and a wide range of geologically and typologically diverse languages with varying histories of language contact. This is the first book that bundles different case studies and systematically investigates the impact of Russian at all linguistic levels, from the lexicon to the domains of grammar to discourse, and with varying types of outcomes such as relatively rapid language shift, structural changes in a relatively stable contact situation, pidginization and super variability at the post-pidgin stage. The volume appeals to linguists studying language contact and contact-induced language change from a broad range of perspectives, who want to gain insight in how one of the largest languages in the world influences other smaller languages, but also experts of mostly minority languages in the sphere of the former Soviet Union"--